Targeted Deletion in the Basal Body Protein Talpid3 Leads to Loss of Primary Cilia in Embryonic Stem Cells and Defective Lineage-Specific Differentiation - Ross Ferguson; Vasanta Subramanian (Cells)
Talpid3 is a basal body protein required for the formation of primary cilia, an organelle involved in signal transduction. Here, we asked if Talpid3 has a role in the regulation of differentiation and/or self-renewal of ES cells and whether cells lacking cilia due to a deletion in Talpid3 can be reprogrammed to induced pluripotent stem (iPS) cells. We show that mouse embryonic limb fibroblasts which lack primary cilia with a targeted deletion in the Talpid3 (Ta3) gene can be efficiently reprogrammed to iPS cells. Furthermore, vector-free Ta3−/− iPS cells retain ES cell features and are able to self-renew. However, both Ta3−/− iPS and ES cells are unable to form visceral endoderm and differentiate poorly into neurons. The observed defects are not a consequence of reprogramming since Ta3−/− ES cells also exhibit this phenotype. Thus, Talpid3 and primary cilia are required for some differentiation events but appear to be dispensable for stem cell self-renewal and reprogramming.